2000
DOI: 10.1136/oem.57.12.793
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a cluster of children with Down's syndrome born to mothers who had attended a school in Dundalk, Ireland

Abstract: Objectives-To investigate a reported cluster of Down's syndrome in oVspring of former pupils of a girls' school in Ireland, to establish the prevalence of Down's syndrome among live births in the area around the school, and to review the literature on the possible causes of reported clusters of Down's syndrome. ), although only four of these mothers were attending the school at any one time. The origin of the non-disjunction was found to be maternal first meiotic in four children, mitotic after fertilisation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…The atomic bomb blasts in Japan at the end of the World War Two and the explosion of the atomic reactor in Chernobyl in 1986 are well-known examples of exposures and have been thoroughly explored. However, they did not lead to an increased birth of children with DS (Dean et al, 2000). Furthermore, neither contact with different organic substances or heavy metals nor an increased consumption of caffeine, alcohol, or nicotine could be shown to increase the number of births of children with trisomy 21 or other chromosome aberrations.…”
Section: Subjects For Discussion On Exogeneous Risk Factorsmentioning
confidence: 96%
“…The atomic bomb blasts in Japan at the end of the World War Two and the explosion of the atomic reactor in Chernobyl in 1986 are well-known examples of exposures and have been thoroughly explored. However, they did not lead to an increased birth of children with DS (Dean et al, 2000). Furthermore, neither contact with different organic substances or heavy metals nor an increased consumption of caffeine, alcohol, or nicotine could be shown to increase the number of births of children with trisomy 21 or other chromosome aberrations.…”
Section: Subjects For Discussion On Exogeneous Risk Factorsmentioning
confidence: 96%
“…In summary, nuclear weapons test participants received the highest radiation doses of any population from nuclear test Studies of environmentally exposed populations and transgenerational effects. Transgenerational studies have been conducted in areas of high natural background radiation in India (Jaikrishan et al 1999) and China (Wei et al 1990) and in areas in Ireland exposed to airborne releases from a nuclear fuel reprocessing plant (Dean et al 2000). The radiation sources in the environment include thoriumcontaining monazite sands and effluents from nuclear facilities (NCRP 2013).…”
Section: Studies Of Cancer Risk Among Environmentally Exposed Populat...mentioning
confidence: 99%
“…An increased rate of Down syndrome among residents in areas of high background radiation in China was later attributed to increased maternal age at birth and to better case ascertainment in the high background radiation areas compared with the control areas (UNSCEAR 1993;Wei et al 1990). Airborne radiation released from the Sellafield nuclear fuel reprocessing plant in England was claimed to have caused a cluster of Down syndrome on the coast of Ireland but was later discounted (Dean et al 2000). Studies of 140,000 inhabitants residing in Kerala, India, in areas of high natural background radiation (15 to 25 mGy annual whole-body dose) reported increased rates of Down syndrome (Kochupillai et al 1976), which were not confirmed in subsequent studies that used more reliable sources of information (Kesavan 1997).…”
Section: Studies Of Cancer Risk Among Environmentally Exposed Populat...mentioning
confidence: 99%
“…Contamination measurements were also made on a daily basis at two Irish sites, namely, Dublin and Valentia. However, the incident did not receive a great deal of public attention in Ireland until almost thirty years later, with the tentative suggestion that there was a link between a cluster of Down's syndrome cases in Dundalk (a town situated on the northeast coast of Ireland) and the Windscale accident ( ).…”
Section: Introductionmentioning
confidence: 99%